Analisis Perhitungan Harga Pokok Produksi Menggunakan Metode Full Costing Pada Warung Boci Raos Teh Een - Nurfitri, Alaisyah; Saputra, Bhagassuci Aji; Aidillah, Dhita; Octaviana, Lisna (CV Warnak Johanna Nusantara, 2025)
This study aims to analyze how Warung Boci Raos Teh Een calculates the cost of production using the full costing approach. The full costing method provides a complete picture of the total costs incurred in the production process, which includes all aspects of production costs, both fixed costs and variable costs. This study uses a qualitative descriptive methodology, where data is collected through documentation, interviews, and observations. In contrast to the calculation approach used by the shop, the research findings state that the full costing method produces more accurate production cost information. Warung Boci Raos Teh Een can improve the effectiveness of cost management and set selling prices strategically with more accurate calculations. It is hoped that small business actors can use this study as a guide to create a pricing strategy based on a comprehensive cost analysis. Based on the analysis using the full costing method, the total production cost in March 2025 was IDR 49,865,000 for 3,000 servings, so the cost per serving was IDR 17,000 (rounded). On the other hand, the internal business calculation only showed a total production cost of IDR 46,565,000, which made the cost of production of 1 serving of baso aci reach IDR 16,000 (rounded). The difference of IDR 1,000 per serving shows that the full costing method produces more accurate and comprehensive calculations, and can be used as a more appropriate reference in determining selling prices and making business decisions in the future.